2017
DOI: 10.1186/s13104-017-3072-0
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing of multiple-sclerosis patients and their unaffected first-degree relatives

Abstract: ObjectivesThe understanding of complex multifactorial diseases requires the availability of a variety of data for a large-number of affected individuals. In this data note here we provide whole exome sequencing data from a set of non-familiar multiple-sclerosis (MS) patients as well as their unaffected first-degree relatives. This data might help the identification of genomic alterations, including single nucleotide polymorphisms, de novo variations and structural genomic variations, such as copy-number altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Genetic studies in MS have used whole exome sequencing (WES) to investigate somatic mutations (Kemppinen et al, 2014), to define the genetic contribution to MS clinical outcomes (Sadovnick et al, 2017) and to suggest new potential causative variants in families (Dyment et al, 2012; Garcia-Rosa et al, 2017; Maver et al, 2017; Mescheriakova et al, 2018) or unrelated patients (Bernales et al, 2018). WES data in families, suggesting monogenic disease forms caused by rare variants with strong functional impact (Ramagopalan et al, 2011; Wang et al, 2016), were not confirmed in the subsequent replication studies (Ban et al, 2013; International Multiple Sclerosis Genetics Consortium, 2016; Minikel and MacArthur, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies in MS have used whole exome sequencing (WES) to investigate somatic mutations (Kemppinen et al, 2014), to define the genetic contribution to MS clinical outcomes (Sadovnick et al, 2017) and to suggest new potential causative variants in families (Dyment et al, 2012; Garcia-Rosa et al, 2017; Maver et al, 2017; Mescheriakova et al, 2018) or unrelated patients (Bernales et al, 2018). WES data in families, suggesting monogenic disease forms caused by rare variants with strong functional impact (Ramagopalan et al, 2011; Wang et al, 2016), were not confirmed in the subsequent replication studies (Ban et al, 2013; International Multiple Sclerosis Genetics Consortium, 2016; Minikel and MacArthur, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A CYP27A1 mutation thought to be related to MS has been described in a family including three patients with the disease (Traboulsee et al, ). Another published study design, using WES to study father‐mother‐child trio, includes 28 patients from eight families; however, the results are not known (García‐Rosa et al, ). The only published study on the subject, evaluating VDR variants in 29 patients with familial MS and comparing them to unrelated controls, found a significant difference between groups for the TaqI variant of VDR (Yucel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Heritability estimates from twin studies on MS genetics propose monozygotic concordance rates of 25-30% with minimal dizygotic concordance rates, suggesting a complex interplay of multiple genetic contributions and environmental influences on disease development (7,25,36,103). To begin understanding these rare polygenic contributions to MS, whole genome/ exome sequencing has begun identifying rare variants that contribute to disease (32,48,61,81). Building a network of genes based on these genetic insights would help in establishing a systems risk assessment while expanding pathways that yield additional rare genetic variants that contribute to MS in a personalized medicine strategy.…”
Section: Introductionmentioning
confidence: 99%